Azospirillum brasilense and Pseudomonas fluorescens applied via foliar application in sorghum cultivar Nucover 100 - Silva, Rogério Soares da; Menezes Filho, Antonio Carlos Pereira de; Batista-Ventura, Hellen Regina Fernandes; Côrrea, Fernando Rezende; Ventura, Matheus Vinicius Abadia (Brazilian Journal of Science, 2022)
Among the microorganisms that promote plant growth, we can highlight the genera Azospirillum and Pseudomonas. These groups of microorganisms can enhance the growth, development and yield of various plant species of agricultural interest. The objective of this study was to verify the efficacy and influence of the commercial product Biofree® based on Pseudomonas fluorescens and Azospirillum brasilense applied via foliar in sorghum. The experiment was carried out at Centro Agro Pesquisa no Cerrado, Rio Verde, Goiás State, Brazil (S 17º44’54" and W 50º51’13"). The treatments consisted of different doses 0.0; 0.3; 0.5 and 0.7 L ha-1 of Biofree® applied via foliar in V4/V5. The variables plant height, panicle size, plant stand, and grain yield were determined. Data were submitted to ANOVA analysis of variance and significance cases were submitted to the Scott-Knott mean test p < 0.05. The application of Azospirillum brasilense and Pseudomonas fluorescens (Biofree®) promoted increases in grain yield of sorghum cultivar Nucover 100.